Innovative activity as a basis for the development of the region - Akhmetova, G.Zh.; Bayneyeva, P.T.; Parmanova, R.S.; Jaworska М. (BUKETOV BUSINESS REVIEW, 2019)
The article examines the issue of forming and developing the potential of a region from the standpoint of introducing the results of innovation activities, examines the historical background of the development of the concept itself from the standpoint of the stages of development of social and production activities, and also forms the mechanism for developing the innovative potential of the region. It is shown that the level of innovation activity can positively affect such aspects of the region as competitiveness, import substitution, as well as the well-being of the population of the region. Particular emphasis is placed on the possibilities of the impact of state structures on the innovative potential of the region. For the regions of Kazakhstan, it is extremely important to create an innovation system aimed at improving the quality of life of the population, as well as reducing the region’s economy from the raw materials orientation. The use of incentive mechanisms for the innovation management system in practice can significantly improve the state of the region’s economy. Particular attention should be paid to the possibility of interfacing the branches of the Republic of Kazakhstan with the world’s leading manufacturers. At the same time, the course should be taken to form a system of advanced development of innovative activity. Such a policy is capable of providing significant advantages in the development of innovative activity in the region. In this case, a lot depends on the steps of the state to support the region. This is both a positive and a negative aspect for the regional economy.